Pelatihan Penerapan Model STEAM-2C Pada Pembelajaran Fisika Bagi Guru SMAN 8 Tanjab Timur - Hendri, Menza; Nehru, Nehru; Pertiwi Rasmi, Dian; Veronika Sirait, Jeliana (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
STEAM (Science, Technology, Engineering, Arts, Mathematics) is a learning approach that can train students to be able to communicate, collaborate, think critically, and solve problems, as well as creativity and innovation so that they are able to face global challenges. The purpose of this community service activity is to train physics teachers of SMAN 8 Tanjung Jabung Timur to use the STEAM-2C model in the learning process. The output produced in this activity is the Student Worksheet based on the STEAM-2C model. The methods used in this activity began with lecture, discussion, question and answer, and assignment methods. After this activity, it is hoped that teachers can integrate the STEAM-2C model in various forms of teaching materials and be able to implement it in learning activities.